A consensus map for quality traits in durum wheat based on genome-wide association studies and detection of ortho-meta QTL across cereal species - Marcotuli, Ilaria; Soriano, Jose Miguel; Gadaleta, Agata (Frontiers in Genetics, 2022)
The present work focused on the identification of durum wheat QTL hotspots from a collection of genome-wide association studies, for quality traits, such as grain protein content and composition, yellow colour, fiber, grain microelement content (iron, magnesium, potassium, selenium, sulphur, calcium, cadmium), kernel vitreousness, semolina and dough quality test. For the first time a total of 10 GWAS studies, comprising 395 marker-trait associations (MTA) on 57 quality traits, with more than 1500 genotypes from 9 association panels, were used to investigate consensus QTL hotspots representative of a wide durum wheat genetic variation. MTA were found distributed on all the A and B genomes chromosomes with minimum number of MTA observed on chromosome 5B (15) and a maximum of 45 on chromosome 7A, with an average of 28 MTA per chromosome. The MTA were equally distributed on A (48%) and B (52%) genomes and allowed the identification of 94 QTL hotspots. Synteny maps for QTL were also performed in Zea mays, Brachypodium, and Oryza sativa, and candidate gene identification allowed the association of genes involved in biological processes playing a major role in the control of quality traits.